Determination of heavy metal concentration in surface and sub surface soil around Ulu Tualang newly-closed Landfill, Temerloh, Pahang - Hairul Ishyam, Hussein (2010)
European community had been stated 13 types of heavy metals that have the highest concern. There were including As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb, Sn, and Tl. Some of these heavy metals such as Cu and Ni are actually necessary to our human body but mostly are very dangerous to our health for example Cu can cause cardiovascular disease while can cause cytotoxic role in plant if in excessive amount. This heavy metal pollution in soil is usually occurring in landfill that near the industrial estate. This situation become worst when there is no proper dumping system in that particular area. So, this research will be conducted to determine the presence and distribution of copper and nickel in surface and sub-surface soils around Ulu Tualang Newly-Closed Landfill, Temerloh, Pahang. This research data will become reference for the landfill management and reconstruction. Samples obtained by digging at different point and two samples for each point, one for surface and one for sub-surface soil. The sample heated using oven, pulverized and sieve to get homogeneity. After that the sample digested using SCL (South California Laboratory) method that used HCl and HNO as the digester. After dilution and vacuum filtered the sample analyzed using Atomic Absorption Spectrophotometry (AAS). For the result, after the sample spiked Cu was detected at 19.2-70.35 mg/kg while Ni was detected around 51.25-99.65 mg/kg. As a conclusion, for the depth differences, the distribution of the heavy metal seems did not have pattern and Ni concentration are higher than copper for both soil layers.